The Role of Religious Extracurricular Program Activities in Fostering Religious Moderation among Students of Public Universities - Septian Arief Budiman; Zohaib Hasan Sain; Wiwit Kurniawan (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2024)
This study explores the role of religious extracurricular activities in fostering religious moderation among university students. In the context of increasing social polarization and extremism, the role of universities in fostering moderate attitudes is crucial. A quantitative approach was used, combining surveys and interviews with 20 students from various faculties, including 10 students who actively participated in religious extracurricular activities and 10 who were not involved. Respondents were aged 18 to 25 and came from various religious backgrounds. The results showed that participation in religious extracurricular activities positively contributed to developing tolerance, empathy, and strengthening of moderation values among university students. The results of this study indicate that extracurricular activities can be an effective means of building a culture of religious moderation, as well as a strategic effort to counteract the potential for radicalization. This study recommends developing more inclusive and dialogue-based extracurricular programs to further promote religious moderation among young people, especially university students.